Peripheral Nerve Injury and Repair - Osbourne, Adam (Trinity Student Medical Journal, 2007)
Peripheral nerve injury can be devastating for a patient. A host of factors influence the highly dynamic degenerative processes that ensue. This article introduces some fundamentals of the mechanisms involved and current treatments available. It serves to highlight some of the more important aspects of the highly sophisticated processes that underlie the pathophysiology of injury and recovery. As will be seen, the regenerative capacity of peripheral nerves is remarkable. Hopefully, a better understanding of the regenerative processes involved will one day assist in the development of new therapies to treat central nervous injury.